Analysis of entrepreneurial resilience as part of the development of entrepreneurship in a learning management model in incubators - Jorge Enrique Taboada-Álvarez; Milton Januario Rueda-Varon; Sandra Jennina Sanchez-Perdomo (Dyna, 2023)
The incubation process of a business idea in its preliminary stages allows a better understanding of the entrepreneur from individual perspectives. However, its study has been limited, generating unsustainability in various ventures. Therefore, business resilience is a key factor for the entrepreneurial spirit, since it allows the entrepreneur to adapt and grow in the face of unexpected changes. The purpose of this research is to analyze entrepreneurial resilience within the framework of a learning management model in incubators. A qualitative approach was obtained through the literature review and a quantitative approach with descriptive, correlational and multivariate statistical analysis. The findings demonstrated that entrepreneurial resilience is decisive in the learning management model in incubators.